Phosphate Yb3+ doped air-cladding photonic crystal fibers for laser applications - Franczyk, Marcin; Stępień, Ryszard; Pysz, Dariusz; Kujawa, Ireneusz; Buczyński, Ryszard (Photonics Letters of Poland, 2014)
We present two single-mode photonic crystal fibers with air-cladding for laser applications. We developed PCF structures created by replacing respectively one and seven air-holes with 6%mol ytterbium doped glass. With increasing mode area you can increase power level and shorten fiber length in laser construction. We achieved 53 and 19 cm optimum length fiber lasers with 4.7 W and 12.4 W respectively maximum output power. The slope efficiency of the lasers were 15.6% and 42.4%. The use of air-cladding brought very high numerical aperture of pump waveguides in both laser fibers resulting with the value of 0.72 and 0.91 respectively. Full Text: PDF References J. Limpert, O. Schmidt, J. Rothhartd, F. Röser, T. Schreiber, A. Tunnermann, "Extended single-mode photonic crystal fiber lasers", Opt. Express 14, 2715 (2006), CrossRef G. Bouwmans, R. M. Percival, W. J. Wadsworth, J. C. Knight, P. St. J. Russell, "High-power Er:Yb fiber laser with very high numerical aperture pump-cladding waveguide", Appl. Phys. Lett. 83, 817 (2003) CrossRef Y. Yeong, J. K. Sahu, D. N. Payne, J. Nilsson, "Ytterbium-doped large-core fiber laser with 1.36 kW continuous-wave output power", Opt. Express 12, 6088 (2004), CrossRef H.Yin, P. Deng, Y. Zhang, F. Gan, "Determination of emission cross section of Yb3+ in glasses by the reciprocity method", Mat.Lett. 30, 29 (1997) CrossRef D.E. McCumber, "Theory of Phonon-Terminated Optical Masers", Phys. Rev. 134, 299 (1964) CrossRef D.E. McCumber, "Einstein Relations Connecting Broadband Emission and Absorption Spectra", Phys. Rev. 136, 954 (1964) CrossRef L. Li et al., "Investigation of modal properties of microstructured optical fibers with large depressed-index cores", Opt. Lett. 30, 3275 (2005) CrossRef W. J. Wadsworth et al.,"Very high numerical aperture fibers", Photonics Techn. Lett. 16, 843 (2004) CrossRef L. Zenteno, J.Lightwave Techn. 11, 1435 (1993) Y. Lee, M. J. F. Digonnet, S. Sinha, KE. Urbanek, R. L. Byer, S. Jiang, JSQE 1, 93 (2009)